Humor Politik dalam Acara E-Talkshow Tv One - arie ramdhan romadoni; Muhammad Fuady (UNISBA Press, 2022)
Abstract. E-Talkshow is a talk show that is very interesting and useful for the millennial generation, where guest stars tell about their lives, and there are always punctuated with humor that is displayed, so that the audience does not feel bored when watching it and makes after watching this event the audience is inspired. from guest stars who are presented and motivated to do something in order to be successful and successful like them. There are not many talk shows in Indonesia that display political humor in it, this event is one of the unique talk shows and attracts public attention which makes the E-Talkshow show a very high rating, the program that airs on TV One is considered able to spoil the audience from boredom. thanks to the cast and guest stars in it. The aim is to find out the connotation signs of political humor in the E-Talkshow Program and to find out the denotation signs of political humor in the E-Talkshow Event. The researcher uses a qualitative method with a semiotic analysis approach of Roland Barthes. Data collection techniques with photos or pictures that the author took screenshots of some of the pieces in this talk show program. The results of this study are that there are several signs of Denotation, Connotation and Myth contained in the talk show whose hosts are Diky Candra and Gracia Indri then the guest star is Mr. Erick Tohir as the Minister of BUMN and the conversation that contains the meaning of the sign of Denotation, Connotation and Myth is wrapped with Humor. where the Host is also a comedian who is able to bring a more fun atmosphere as for the form of political humor that is present during the conversation in the talk show is a form of satire, satire, and humor in it. Abstrak. E-Talkshow merupakan acara talk show yang sangat menarik dan bermanfaat bagi generasi millennial, dimana bintang tamu menceritakan tentang kehidupan nya, dan disitu selalu diselingi dengan humor yang di tampilkan, sehingga membuat penonton tidak merasa bosan ketika menontonnya dan membuat setelah menonton acara ini penonton terinspirasi dari bintang tamu yang dihadirkan dan termotivasi untuk melaksanakan suatu hal supaya bisa berhasil dan sukses seperti mereka. Tidak banyak acara talk show di Indonesia yang menampilkan humor politik didalamnya, acara ini adalah salah satu acara talk show yang unik dan menarik perhatian publik yang menjadikan rating acara E-Talkshow sangat tinggi, acara yang tayang di TV One ini dinilai mampu memanjakan penonton dari kejenuhan berkat pemain dan bintang tamu didalamnya. Tujuannya untuk mengetahui tanda konotasi humor politik dalam Acara E-Talkshow dan untuk mengetahui tanda denotasi humor politik dalam Acara E-Talkshow. Peneliti menggunakan metode kualitatif dengan pendekatan analisis semiotika Roland Barthes. Teknik pengumpulan data dengan foto atau gambar yang penulis Screenshot beberapa potongan dalam programa acara talkshow ini. Hasil dari penelitian ini adalah ada beberapa tanda Denotasi,Konotasi dan Mitos yang terkandung dalam talkshow yang host nya adalah Diky Candra dan Gracia Indri lalu bintang tamunya Bapak Erick Tohir selaku Menteri BUMN dan percakapan yang mangadung makna tanda Denotasi,Konotasi dan Mitos tersebut dibalut dengan Humor yang dimana sang Host pun seorang Komedian yang mampu membawakan suasan lebih fun adapun wujud dari humor politik yang ada saat perbincangan dalam talkshow tersebut adalah wujud satir, sindiran, dan juga humor didalamnya.